2011
DOI: 10.2174/1874088x01105010083
|View full text |Cite
|
Sign up to set email alerts
|

Low-Melting CaCl2-NaCl-Al2O3 Electrolyte for Direct Electrochemical Reduction Solid Al2O3

Abstract: Abstract:The electrical conductivity and density of the low-melting CaCl 2 -NaCl-Al 2 O 3 systems at 550°C~800°C ranges were respectively measured by the Continuously Varying Cell Constant Technique, ac-techniques and Archimedes method. The materials were applied as the electrolyte for the direct electrochemical reduction solid Al 2 O 3 at 550°C ~800°C. The materials were composed of 71wt.%~87wt.%CaCl 2 (corresponding NaCl), NaCl and Al 2 O 3 (without and saturated). The results showed that additive Al 2 O 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…). Addition of yttria in salt perhaps decreases the electronic conductivity in salt, preventing the electrochemical reduction of zirconia and thereby microchannels are not developed inside the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…). Addition of yttria in salt perhaps decreases the electronic conductivity in salt, preventing the electrochemical reduction of zirconia and thereby microchannels are not developed inside the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to SiO2, Grambalova et al [33] reported that K + -and Na + -based molten salts interact chemically with Al2O3. Treatment of Al2O3 with a CaCl2-NaCl containing electrolyte leads to the electrochemical reduction of Al2O3, which becomes stronger at higher concentrations of NaCl [36]. Lee et al [37] reported that the native aluminium oxide film on Al dissolves faster in contact with more basic solutions that contain more Na + salts.…”
Section: (C) Max Phase-based Ceramicsmentioning
confidence: 99%
“…Meanwhile, electrolytic reductions of various kinds of solid oxides in CaCl 2 and/or CaCl 2 -based molten salts have been investigated by many researchers in the last two decades. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Fray et al reported the direct electrolytic reduction of TiO 2 pellets in a CaCl 2based melt, known as the FFC Cambridge process. [1][2][3][4][5][6] This process has the potential to replace the conventional Kroll process for producing Ti metal, owing to its simple system and relatively low temperature.…”
mentioning
confidence: 99%
“…For the electrochemical reduction of Al 2 O 3 , there have been several studies conducted in CaCl 2 -based melts. [13][14][15][16][17] Yan investigated the reduction of Al 2 O 3 tube using a Nb box-type cathode in molten CaCl 2 -NaCl at 1173 K. 13 In this study, Al-rich Al-Ca alloy droplets with 84.9-98.4 at%Al was obtained. Yan and Fray also reported the electrochemical reduction of Al 2 O 3 in CaCl 2 -LiCl at 973 K and CaCl 2 -NaCl at 1173 K. 15 They reported that calcium aluminate was formed as an intermediate product during the electrolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation